Molecular Identification of E. coli Virulence Factors Genes, bfp and elt, in Feces of Diarrheic Chickens - N. Sadeq, Jinan; A.A. Al-Mohamed, Saba; M. Salim, Rana (Al-Qadisiyah Journal of Pure Science, 2018)
The study was aimed to demonstrate the existence of major virulence factors bfp and elt genes for enteropathogenic E. coli (EPEC) and enterotoxogenic E. coli (ETEC), respectively, in feces of diarrheic chicken by using PCR technique. For this purpose, 50 diarrheic chickens were subjected for fecal samples collection. In first, the samples have been cultured on MacConkey and Eosin Methylene Blue agars, and the isolates were tested by some specific biochemical tests to verify of E. coli samples, which revealed on 20 positive samples. The twenty positive samples were submitted, only, for PCR technique to confirm the existence of elt and bfp genes. With genes detection, the overall results of the present study were showed that 11/50 (22 %) and 7/50 (14 %) were positives for EPEC-bfp and ETEC-elt genes, respectively. Also, the cross-infections results with bfp and elt genes had been identified that 5/20 (25%) were positives with both genes, 2/20 (10 %) were positives with elt gene, only, and 6/20 (30%) were positives with bfp gene, only. Statistically, the significant differences were reported between the prevalence rates of bfp and elt genes, at a level of PÂ£0.05.